Heptacoordinate CoII Complex: A New Architecture for Photochemical Hydrogen Production. Issue 28 (2nd May 2017) - Lucarini, Fiorella; Pastore, Mariachiara; Vasylevskyi, Serhii; Varisco, Massimo; Solari, Euro; Crochet, Aurelien; Fromm, Katharina M.; Zobi, Fabio; Ruggi, Albert
Abstract: The first heptacoordinate cobalt catalyst for light‐driven hydrogen production in water has been synthesized and characterized. Photochemical experiments using [Ru(bpy)3 ] 2+ as photosensitizer gave a turnover number (TON) of 16300 mol H2  (mol cat.) −1 achieved in 2 hours of irradiation with visible (475 nm) light. This promising result provides a path forward in the development of new structures to improve the efficiency of the catalysis. Abstract : Seven is better than six ! The first heptacoordinate cobalt catalyst capable of performing light‐driven hydrogen production in water is described. Photochemical experiments gave a turnover number (TON) of 16300 mol H2 (mol cat.) −1 achieved in two hours of irradiation with visible (475 nm) light. The results suggest that heptacoordinate cobalt complexes represent a promising alternative platform for the development of highly active photocatalysts.